Fixed-Bed Adsorption of Phenol onto Microporous Activated Carbon Set from Rice Husk Using Chemical Activation - Daffalla, S.B. (MDPI, 2022)
In the course of this research, the potential of activated carbon from rice husk was examined as being a phenol removal medium from an aqueous solution in a fixed-bed adsorption column. The activated carbon was characterized through FESEM (Field-Emission Scanning Electron Microscopy) and BET (BrunauerâEmmettâTeller) surface area. According to the FESEM micrograph and BET surface area, RHAC (rice husk activated carbon) had a porous structure with a large surface area of 587 m2Â·gâ1 and mean diameter of pores of 2.06 nm. The concentration effects on the influent phenol (100â2000 mgÂ·Lâ1 ), rate of flow (5â10 mLÂ·minâ1 ), and bed depth (8.5â15.3 cm) were examined. It was found that the capacity of bed adsorption increased according to the increase in the influent concentration and bed depth. However, the capacity of bed adsorption decreased according to the increase in the feed flow rate. The regeneration of activated carbon column using 0.1 M sodium hydroxide was found to be effective with a 75 regeneration efficiency after three regeneration cycles. Data on adsorption were observed to be in line with many well-established models (i.e., YoonâNelson and AdamsâBohart, as well as bed depth service time models). Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.